Supposing that the equation that you want to solve is `2x + sqrt(3x-2) = 3` , then you need to isolate square root to the left side such that:

`sqrt(3x-2) = 3 - 2x`

You need to raise to square both side to remove the square root such that:

...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Supposing that the equation that you want to solve is `2x + sqrt(3x-2) = 3` , then you need to isolate square root to the left side such that:

`sqrt(3x-2) = 3 - 2x`

You need to raise to square both side to remove the square root such that:

`3x - 2 = (3 - 2x)^2`

You need to expand the binomial such that:

`3x -2 = 9 - 12x + 4x^2`

`4x^2 - 12x + 9 - 3x + 2 = 0`

`4x^2 - 15x + 11 = 0`

You need to use quadratic formula such that:

`x_(1,2) = (15+-sqrt(225 - 176))/8`

`x_(1,2) = (15+-sqrt49)/8`

`x_(1,2) = (15+-7)/8 =gt x_1 = (15+7)/8 = 11/4`

`x_2 = (15-7)/8 = 1`

Notice that both solutions check the square root.

**Hence, evaluating soultions to equation yields `x_1 = 11/4` and `x_2 = 1` .**